Parasitoid-mediated effects: Apparent competition and the persistence of host-parasitoid assemblages - Bonsall, M; Hassell, M (1999)
Indirect effects such as apparent competition (in which two hosts that do not compete for resources interact via a shared natural enemy) are increasingly being shown to be prevalent in the structure and function of ecological assemblages. Here, we review the empirical and theoretical evidence for these enemy-mediated effects in host-parasitoid assemblages. We first address questions about the design of experiments to test for apparent competition. Second, we consider factors likely to affect the coexistence of host species that share a parasitoid and are involved in apparent competition. We show that parasitoid aggregation, and the switching effect that this can generate when hosts occur in separate patches, not only promotes persistence but is also strongly stabilizing. The broader consequences of these effects are discussed.